Teorija argumentacije Oswalda Ducrota - Puc, David (Jezik in slovstvo, 2005)
The article aims to show the theory of argumentation by the French linguist and philosopher Oswald Ducrot. Based on the structural difference between a sentence and a utterance, the author in a critical dialogue with the traditionof speech acts develops a new theory of argumentation - " the theory of argumentation in the language system". With this theory Ducrot researches the argumentative potential of the language as a system and shows that certain argumentative features are already written into the language as a system. Argumentation is not based on facts and logical deducation, it is written into the so-called argumentative operators (certain cojunctions, particles and verbs). In the final part of the article Ducrot's theory of argumentation is applied to the text type of commnetary, while guidelines for further development of the topos theory are also provided.
Keywords: Ducrot, Oswald; linguistics; lingvistika; filozofija jezika; argumentacija; francoski filozofi